Evaluasi Beban Kerja Mental Pekerja yang Terpapar Kebisingan pada Perusahaan Mebel - Kontesya, Kamelia; Sari, Andesi Purnama; Ridhana, Ihsan; Adelino, Muhammad Ilham (Engineering Faculty at Universitas Singaperbangsa Karawang, 2024)
The furniture industry focuses on producing frames, panel doors, windows, and various furniture variations. During its operations, a significant portion of the work involves the use of tools or machines that generate loud noise and require substantial effort. The objective of this research is to identify categories of mental workload on workers and propose feasible improvements. The methods used were the National Aeronautics and Space Administration-Task Load Index (NASA-TLX) and the Rating Scale Mental Effort (RSME). All workers were actively engaged in this study. The results found that all workers were categorized into high and very high levels with a workload score range of 62.67-81.33. The highest influencing indicator was performance (25.45%). These findings were corroborated by the RSME results, where the average score falls within the range of 70-90 out of 150. Based on these results, improvements could be made by increasing the number of workers for job rotation.